Women in archaeology - Claassen, Cheryl 1953-. (Philadelphia University of Pennsylvania Press, 1994)
"Pt. 1 of this collection presents a history of women in Americanist archaeology, including a biography of Dorothy Hughes Popenoe who conducted early stratigraphic excavations in Honduras. Pt. 2 focuses on the current status of North American women in Mesoamerican archaeology and problems of gender bias. Valuable discussion of issues, but non-US archaeologists are not covered"--Handbook of Latin American Studies, v. 57. |u http://www.loc.gov/hlas
ASP-1137g donated by Dr. William A. Longacre on July 16, 2012.
Keywords: Women archaeologists -- United States -- Biography; Women archaeologists -- United States